SISTEM PERANCANGAN JUAL BELI KENDARAAN DENGAN MENGGUNAKAN METODE AGILE SOFTWARE DEVELOPMENT BERBASIS WEB (STUDI KASUS SHOWROOM ALDI MOTOR) - Dian Sopyandi; Deri Andragi; Rifky Firmansyah; Roeslan Djutalov (Journal of Research and Publication Innovation, 2023)
Abstract Aldi Motor Showroom is a company that sells and buys used motorcycles from various brands and types of motorbikes, this showroom requires media to carry out product promotion and marketing. As technology develops, it is necessary to create website-based media promotion and sales. This promotional and marketing media contains product information and specifications as well as profiles that will be used to assist in the promotion and delivery of information. Marketing that still relies on word of mouth and only by distributing brochures and limited partners with additional costs, promotions tend to be less effective and their reach is still limited to certain locations. The purpose of this research is to design a web-based used motorcycle sales system. Planning for this sales information system uses the Agile Software Development development method.